The comparative analysis and health concerns of recently emerged sub-lineages of Omicron, which have led to rising cases of COVID-19 in the Indian population in 2023 - Amrita Panja; Biplab Kahar (Asian Journal of Medical Sciences, 2026)
The present World is facing unpredictable health problems generated by different variants of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Continuous evolution of SARS-CoV-2 has contributed to develop new subvariants, including BQ.1, BQ.1.1, BA.4.6, BF.7, and BA.2.75.2. Each sub lineages are little different from each other depending upon the mutations during their genome replication. There is a vital role of mutations in transmissibility and virulence of SARS-CoV-2. XBB.1.16 lineage has seemed as the most widely spread lineage in India and is causing an upsurge in COVID-19 cases at the beginning of the year 2023 in the Indian population. Another sub-lineage, BA.2.86, was first recognized in August 2023, and it is quite divergent from the presently circulating SARS-CoV-2 lineages. Unlike the other Omicron variants, it carries 30 mutations in the spike (S) protein, which within the host body. With due course of time, JN.1 (BA.2.86.1.1) has appeared from BA.2.86 in late 2023. S: L455S is regarded as the signature mutation of JN.1 along with three other mutations in non–spike proteins. Another mutation, S: L455F, is responsible for increased transmissibility and is present in HK.3 and other “Flip” variants. Here, in this paper, we have investigated the epidemiology, virological properties, and characteristic features of different sub-lineages of Omicron, which have been dominated throughout the year 2023 in the Indian population. Proper knowledge regarding protein structure, diagnosis, spreadability, treatment, and potency of vaccines is urgent for the proper control and prevention of SARS-CoV-2.